Actor Networks and Public Sentiment in the Cancel Culture Phenomenon: A Social Network Analysis of A Business Proposal Remake in Indonesia - Suaib, Nadinta Rafifah; Ritonga, Rajab; Ningsih, Tri Wahyu Retno (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Cancel culture has become a significant influence in Indonesia’s digital entertainment sphere. This study investigates how the cancel culture surrounding the Indonesian remake of A Business Proposal emerges and diffuses across social media networks. This study aims to identify network structures, central actors, and the dissemination of moral discourse among users. This study uses a social network analysis approach supported by sentiment and lexical analyses from 515 tweets, which were harvested using a Python-based script from the 1st of January until the 19th of February 2025, and visualized using Gephi. Data were cleaned (deduplication, language filtering, token cleaning), a user–interaction network was constructed, and centrality plus community detection were applied. The findings reveal five major clusters and a zero betweenness value, indicating strong interconnectedness and the absence of intermediaries. The dominant cluster, led by kdrama_menfess, amplified evaluative narratives shaped by fandom identity and cultural expectations. Sentiment is largely neutral, with salient negative cues tied to casting and adaptation quality. Cancel culture here functions as networked moral regulation driven by fandom solidarity and enabled by Computer-Mediated Communication within Castells’ Network Society. The findings clarify how audience expectations, affect, and network structure jointly shape acceptance of local adaptations, offering practical cues for casting, promotion, and community management in Indonesia’s film industry.